(untitled) (Journal of Dhaka Medical College, 2016)
Context: The kidney is a highly vascular organ in the human body. The aim of the present study was to see the variations in perihilar branching pattern and morphology of the main renal arteries in a Bangladeshi population based on autopsy. Methods: This cross-sectional, descriptive study was done in the Department of Anatomy, Dhaka Medical College, Dhaka, from July 2008 to June 2009, based on collection of 140 post mortem human kidneys from 70 unclaimed dead bodies which were in the morgue. All the samples were divided into three age-groups: A (10-19 years), B (20-39 years) and C (40-59 years). Morphological examination was done to identify main renal arteries and accessory renal arteries with their sites of origin and perihilar branching pattern of the renal arteries as well. The length of the renal artery was measured by using a measuring tape. Besides, renal angiography was done to see the intrarenal branching pattern. Results: The length of the right and left renal arteries were found 3.09±0.08 cm and 2.09±0.09 cm; 3.48±0.17 cm and 2.34±0.17 cm; 3.88±0.17 cm and 2.81±0.16 cm in group A, B and C respectively. The length of the right renal artery was found greater than of the left (P<0.001) in all age-groups. Besides, age related changes were also found in the length of the renal arteries (P<0.001). Accessory renal arteries were present in the right side in 33.4%, 23.35 and 33.3% specimens in group A, B and C respectively, while in the left side, in 59.7%, 27.9% and 13.4% in group A, B and C respectively. The number of anterior divisions of the both renal arteries were 2 in 8.3%, 3 in 12.5% and 4 in 79.2% specimens in group A, while in group B, 2 in 7%, 3 in 17.4% and 4 in 75.6% specimens, and in group C, 2 in 3.3%, 3 in 3.3% and 4 in 93.3% specimens. Number of posterior division was found only 1 in all the groups. Renal angiography revealed intrarenal branching pattern which showed segmental arteries divided into several lobar arteries and interlobar arteries. J Dhaka Medical College, Vol. 24, No.1, April, 2015, Page 12-16